The Build and Bond: A team exercise - Rebecca L. Wyland; Nancy J. Hanson-Rasmussen; Daniel P. Gullifor (Organization Management Journal (OMJ), 2023)
Purpose - The purpose of this paper is to present The Build and Bond, an experiential exercise which engages student teams while they apply team dynamics, enhance team skills and foster team member interpersonal bonds. Design/methodology/approach - During The Build and Bond, teams design and execute their own team-building activity. Specifically, teams set goals, generate ideas, make decisions, create a team-building activity, develop implementation plans and ultimately execute the activity. Finally, during an all-class debrief discussion, teams describe their team-building activities, connect their experiences to the learning objectives and reflect on how these lessons can be applied in future team experiences. Pretest and posttest surveys were used to determine if participants perceived increases in team performance and cohesion following The Build and Bond. Findings - All teams reported that their activity added value, was preferred over an instructor-assigned team-building activity and improved team states. Findings from t-tests supported an improvement in team performance and cohesion. Social implications - The Build and Bond is designed to help students feel more equipped to communicate, have fun and work interdependently with current and future team members. Originality/value - Teams design the team-building activity themselves, so members are often more interested in participating and engaging during the team-building activity.
Keywords: 650; Experiential exercise; Student project teams; Team building; Team member bonds; Virtual teams